La robótica educativa como recurso tecnológico innovador para potenciar el razonamiento lógico, la creatividad y el aprendizaje significativo en la asignatura de Matemáticas para los niños del segundo año de educación básica de la escuela Lauro Damerval Ayora N1 - Hurtado González, Jenny Marisol (2015)
The lack of updated technological tools and ignorance in its management by teachers causes the teaching - learning in the area of mathematics is dull and unattractive to students, likewise disregard for authority to update the methodology education at par with the technological advances prevents critical development of their students. The development project is aimed to contribute to the Region Seven Loja Canton, students of second year of basic education school Lauro Damerval Ayora No.1 to bring each one to develop their creativity and logical reasoning and learning can have a significant in the field of Mathematics. Initially observing the work of children in the classroom was performed to distinguish the methodology used, then an interview with the teacher and authorities on the technological tools used to motivate students in learning mathematics was made. The basic kit plus Lego wedo software is intended to be a support tool for teaching, where children build models with simple sensors and a motor that is connected to their computers. This tool turned attractive to children (as) that stimulates a fun way of learning